Screw Fixation Versus Hemiarthroplasty for Nondisplaced Femoral Neck Fractures in the Elderly: A Cost-Effectiveness Analysis. Issue 7 (July 2020) - Yong, Taylor M.; Austin, Daniel C.; Molloy, Ilda B.; Kunkel, Samuel T.; Jevsevar, David S.; Gitajn, Ida L.
Abstract : Objective: To evaluate the cost-effectiveness of screw fixation versus hemiarthroplasty for nondisplaced femoral neck fractures in low-demand elderly patients. Methods: We constructed a Markov decision model using a low-demand, 80-year-old patient as the base case. Costs, health-state utilities, mortality rates, and transition probabilities were obtained from published literature. The simulation model was cycled until all patients were deceased to estimate lifetime costs and quality-adjusted life years (QALYs). The primary outcome was the incremental cost-effectiveness ratio with a willingness-to-pay threshold set at 100, 000 per QALY. We performed sensitivity analyses to assess our parameter assumptions. Results: For the base case, hemiarthroplasty was associated with greater quality of life (2.96 QALYs) compared with screw fixation (2.73 QALYs) with lower cost (23, 467 vs. 25, 356). Cost per QALY for hemiarthroplasty was 7925 compared with 9303 in screw fixation. Hemiarthroplasty provided better outcomes at lower cost, indicating dominance over screw fixation. Conclusions: Hemiarthroplasty is a cost-effective option compared with screw fixation for the treatment of nondisplaced femoral neck fractures in the low-demand elderly. Medical comorbidities and other factors that impact perioperative mortality should also be considered in the treatment decision. Level of Evidence: Economic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.